HDAC Inhibition as Neuroprotection in COVID-19 Infection - Sixto-López, Yudibeth; Correa-Basurto, José (Current Topics in Medicinal Chemistry, 2022)
The SARS-CoV-2 virus is responsible for COVID-19 affecting millions of humans around the world. COVID-19 shows various clinical symptoms (fever, cough, fatigue, diarrhea, body aches, headaches, anosmia, and hyposmia). Approximately 30% of patients with COVID-19 showed neurological symptoms, from mild to severe manifestations including headache, dizziness, impaired consciousness, encephalopathy, anosmia, hypogeusia, and hyposmia, among others. The neurotropism of the SARS-CoV-2 virus explains its neuroinvasion provoking neurological damage such as acute demyelination, neuroinflammation, etc. At the molecular level, the COVID-19 patients had higher levels of cytokines and chemokines known as cytokines storms which disrupt the blood-brain barrier allowing the entrance of monocytes and lymphocytes, causing neuroinflammation, neurodegeneration, and demyelination. In addition, the proinflammatory cytokines have been observed in ischemic, hemorrhagic strokes, seizures, and encephalopathy. In this sense, early neuroprotective management should be adopted to avoid or decrease neurological damage due to SARS-CoV-2 infection. Several approaches can be used; one of them includes using HDAC inhibitors (HDACi) due to their neuroprotective effects. Also, the HDACi down-regulates the proinflammatory cytokines (IL-6 and TNF-α) decreasing the neurotoxicity. HDACi can also avoid and prevent the entrance of the virus into the central nervous System (CNS) and decrease the virus replication by downregulating the virus receptors. Here we review the mechanisms that could explain how the SARS-CoV-2 virus could reach the CNS, induce neurological damage and symptoms, and the possibility to use HDACi as neuroprotective therapy.
Keywords: Neurological symptoms